Kontinuitas dan Perubahan dalam Penetapan Hukum Hudud: Dari Nass hingga Teks Fikih - Sodiqin, Ali (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
Hudud law is a part of Islamic criminal law besides the law of qişaş and ta'zir. Historically and anthropologically, the enforcement of this law has something to do with the continuity of pre-Islamic legal tradition. Al-Quran responds to this legal tradition through two models, namely tahrim (destructive) and taghyir (reconstructive). Tahrim happens in the case of khamr (intoxicating liquor), whereas the taghyir occurs on the law of theft, adultery, and qażaf (accused of adultery). AlQur'an reconstructs laws of the past, so its entry is based on the world view of the Qur'an. Philosophical values embodied in the hudud law is justice, responsibility, morality, and equality. All these values are the basis for law enforcement, so the law enforcement model is reformative and restorative. The construction of scholars' thoughts in the determination of hudud law can be divided into two forms, textualist and contextualist. Textualist especially concerning the establishment of a form of punishment for violators of hudud. The scholars define such penalties as it is written in the texts. Contextualist contains in the details of the requirements in the application of hudud law. The jurists formulate prerequisites and various procedures required in order to implement hudud law through the courts. In this context, the scholars consider the needs of the community in terms of law enforcement. The diversity of opinions of the jurists due to the diversity of the proposition and the fatwa is used as a legal considerations, besides using the methodology of legal reasoning in understanding the legal texts about hudud.